2002
DOI: 10.1080/00087114.2002.10797889
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome numbers in the genusLychnophoraMart. (Lychnophorinae, Vernonieae, Asteraceae)

Abstract: The genus Lychnophora Mart. comprises about 68 endemic species in "campos rupestres" in the States of Minas Gerais, Bahia and Goias. Ecological conditions of this environment possibly favored an intense speciation, and could be one factor for this endemism. The highest diversity is found in Minas Gerais, a state also considered as the major center of dispersal of this genus. To contribute to the biosystematic study of the genus, we carried out a chromosomic study in 18 species of Lychnophora, belonging to 3 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
29
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 18 publications
8
29
0
2
Order By: Relevance
“…The genus Lychnophora (Asteraceae) is endemic in the central region of Brazil, mainly in rupestral fields in the states of Minas Gerais, Goiás, and Bahia (Robinson, 1999). This genus comprises 68 species (Mansanares et al, 2002) and some of them are listed as species threatened with extinction . Lychnophora species are popularly used to treat wounds, bruise, pain, rheumatism, and inflammation (Borsato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Lychnophora (Asteraceae) is endemic in the central region of Brazil, mainly in rupestral fields in the states of Minas Gerais, Goiás, and Bahia (Robinson, 1999). This genus comprises 68 species (Mansanares et al, 2002) and some of them are listed as species threatened with extinction . Lychnophora species are popularly used to treat wounds, bruise, pain, rheumatism, and inflammation (Borsato et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most of its genera is found on the Brazilian's rupestrian vegetation (Table 1), which is present on the top of mountain chains on the Central and Southeastern regions of Brazil, especially in Minas Gerais, Bahia and Goiás, all presenting many species 1 with a high degree of endemism. Due to the taxonomic complexity of the Lychnophorinae, the genera of this subtribe have received considerable attention and several previous classification had to be changed.…”
Section: Introductionmentioning
confidence: 99%
“…According to Jones (1979), polyploids are very frequent in the New World and the most common basic chromosome number is x 2 = 17, while the Old World species present usually basic number x 1 = 9 and x 1 = 10 and polyploids are not frequently observed. Nevertheless, the more recent chromosome studies in New World species of the tribe have found other basic chromosome numbers such as x 1 = 9, x 1 = 10, x 1 = 12, x 1 = 14, x 2 = 15, x 2 = 16, x 2 = 17, x 2 = 18, x 2 = 19 and x 2 = 31 (Turner 1981;Ruas et al 1991;Dematteis 1998;Mansanares et al 2002;Dematteis 2009, 2012;Salles de Melo et al 2010). The ancestral basic chromosome number in the Vernonieae is considered to be x 1 = 9 or x 1 = 10, as reported for African and Asian species of the tribe (Jones 1979).…”
Section: Introductionmentioning
confidence: 99%